PENGARUH KERAMAHAN, KECEPATAN LAYANAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI ALFAMART - Permata, Rizqi Rika; Werdiasih, Rustina Dewi; Karnowati, Nandang Bekti (JURNAL EKONOMI, 2024)
This study aims to examine the effect of Hospitality (X1), Service Speed (X2) and Promotion (X3) on Consumer Purchase Decisions (Y) at Alfamart. The sample in this study was Alfamart consumers totaling 108 respondents with a sampling technique using the Lemeshow formula. Data collection techniques are carried out by distributing questionnaires to Alfamart consumers. Analysis prerequisite tests include linearity test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test. Data analysis techniques with multiple linear regression, statistical tests through T test, F test as well as R2 test and classical assumption test.The results showed that: (1) Friendliness had no effect on purchasing decisions; (2) Speed of service affects purchasing decisions; (3) Promotions affect purchasing decisions; (4) Friendliness, speed of service and promotion simultaneously influence the purchase decision.